Premedication Methods in Nasal Endoscopy: A Prospective, Randomized, Double-Blind Study - Mehmet İlhan Şahin; Kerem Kökoğlu; Şafak Güleç; İbrahim Ketenci; Yaşar Ünlü (Clinical and Experimental Otorhinolaryngology, 2017)
Objectives To identify the optimal pharmacological method of preparing patients for nasal endoscopy. Methods Twenty healthy volunteers were enrolled in this prospective, randomized, double-blind study. Four types of medications were applied in their nostrils with binary combinations of spray bottles on four different days in a random order: placebo (normal saline [NS]+NS), decongestant (NS+oxymetazoline), anesthetic (NS+lidocaine), and decongestant plus anesthetic (oxymetazoline+lidocaine). Rigid nasal endoscopy was performed 10 minutes after spray application. The volunteers evaluated the discomfort caused by each spray application, and nasal pain scores due to the passage of the endoscope. The physicians quantified nasal decongestion using a visual analogue scale. Endoscopy duration as well as pulse and mean blood pressure (MBP) before spray application, 10 minutes after the application, and immediately after endoscopic examination were also recorded. Results The discomfort caused by lidocaine was significantly higher than that caused by the other sprays (P<0.001). The lowest pain score related to endoscopy was obtained for oxymetazoline+lidocaine (P<0.001). Nasal decongestion was best achieved with NS+oxymetazoline (P<0.001). Endoscopy duration was the shortest for oxymetazoline+ lidocaine (P<0.05). Statistically significant MBP changes were only seen with the application of NS+oxymetazoline (P<0.05). However, neither MBP nor pulse rate change was significant clinically. Conclusion Application of decongestant and anesthetic sprays together seems to be the best method of pharmacological preparation of patients for nasal endoscopy.